2005
DOI: 10.1186/1471-2407-5-68
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of cathepsin f, matrix metalloproteinases 11 and 12 in cervical cancer

Abstract: Background: Cervical carcinoma (CC) is one of the most common cancers among women worldwide and the first cause of death among the Mexican female population. CC progression shows a continuum of neoplastic transitions until invasion. Matrix metalloproteinases (MMPs) and cathepsins play a central role on the enhancement of tumor-induced angiogenesis, cell migration, proliferation, apoptosis and connective tissue degradation. MMPs -2 and -9 expression has been widely studied in cervical cancer. Nevertheless, no o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 34 publications
6
61
3
1
Order By: Relevance
“…Similar to AKT, MMP3 can also cause epithelial -mesenchymal transition in cancer (Radisky et al, 2005). Matrix metalloproteinase 9 plays a central role in connective tissue degradation, tumourinduced angiogenesis, cell proliferation/apoptosis and cell migration in various tumour types including cervical cancer (van Kempen and Coussens, 2002;Van Trappen et al, 2002;Zucker and Vacirca, 2004;Vazquez-Ortiz et al, 2005b). Recently, one study has shown that MMP9 forms a complex with the hyaluronan receptor CD44 on the surface of breast cancer cells and activates downstream TGF-b, facilitating tumour cell survival, invasion and metastasis (Yu and Stamenkovic, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to AKT, MMP3 can also cause epithelial -mesenchymal transition in cancer (Radisky et al, 2005). Matrix metalloproteinase 9 plays a central role in connective tissue degradation, tumourinduced angiogenesis, cell proliferation/apoptosis and cell migration in various tumour types including cervical cancer (van Kempen and Coussens, 2002;Van Trappen et al, 2002;Zucker and Vacirca, 2004;Vazquez-Ortiz et al, 2005b). Recently, one study has shown that MMP9 forms a complex with the hyaluronan receptor CD44 on the surface of breast cancer cells and activates downstream TGF-b, facilitating tumour cell survival, invasion and metastasis (Yu and Stamenkovic, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…53 Although only little data are available on Cathepsin F, several human cancer cell lines have increased expression of CTSF compared with its normal counterpart, suggesting that this enzyme could be involved in degradative processes during tumor progression. [53][54][55] Cathepsins are a class of globular proteases that were initially described as intracellular peptide hydrolases, although several cathepsins also have extracellular functions. Most studies have confirmed that cathepsins are highly expressed in invasive tumors, and they mediate degradation of the ECM and collagen, increase the motility and invasion of cancer cells, mediate the dissemination of cancer cells, and induce the EMT and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…6 MMP12 is overexpressed in cervical scrape cells from cervical precursor lesions, 7 and contributes to the pathogenesis of cervical cancer. 8 In addition, MMP-12 polymorphism is connected with a higher risk of disseminated colorectal cancer (CRC) 9 and lung cancer, 10 and indicates a poor prognosis in breast cancer 11 and esophageal adenocarcinoma. 12 Functionally, MMP12-induced myeloid cell autonomous defect leads to abnormal myelopoiesis, immune suppression, and tumorigenesis of LAC.…”
mentioning
confidence: 99%